Trophic ecology of the yellowfin notothen, Patagonotothen guntheri (Norman, 1937) at the Marine Protected Area Namuncurá-Burdwood Bank, Argentina - Covatti Ale, Marina; Fischer, Luciana Stefania; Deli Antoni, Mariana Yanel; Díaz de Astarloa, Juan Martín; Delpiani, Gabriela Elina (Polar Biology)
The yellowfin notothen Patagonotothen guntheri is an important fish species in the Marine Protected Area Namuncurá-Burdwood Bank (MPAN-BB) due to its high abundance and significant ecological role. Thus, diet composition and feeding habits were analyzed. To fulfill this purpose, percentage frequency of occurrence, prey-specific abundance, and prey-specific index of relative importance (%PSIRI) were calculated. Generalized linear models were built for the defined prey categories to assess changes in feeding associated with total length, sex, depth, and zone of capture. Two hundred fifty-two specimens were sampled (69–256 mm total length), of which 186 contained food (73.41%). According to PSIRI, ophiuroids (23.28%), unidentified polychaetes (17.92%), and Munida gregaria (12.73%) were the main prey items. However, yellowfin notothen showed variations in diet composition according to their length and the depth of capture. The consumption of decapods and other invertebrates increased with depth, while the ingestion of ophiuroids decreased. Also, the number of polychaetes was higher in the stomach content of larger specimens. The present work provides the first description and analysis of P. guntheri trophic ecology in the MPAN-BB, concluding that it is a species with a generalist diet, which feeds on a great diversity of both benthic and pelagic organisms depending on availability. Fil: Covatti Ale, Marina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Fischer, Luciana Stefania. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto de Investigaciones ...